HIERARCHICAL WITH STRONG AUTHENTICATION REDUCTION SCHEME IN MANETS (International Journal of Engineering and Computer Science, 2013)
Many existing reputation systems sharply divide the trust value into right or wrong, thus ignoring another core dimension of trust: uncertainty. As uncertainty deeply impacts a node’s anticipation of others’ behavior and decisions during interaction. Besides lacking a precise semantic, this information has abstracted away any notion of time. This approach is objective and robust. But, this approach still leaves an opportunity for elaborate attackers to launch false accusation attacks since there is no constraint on update frequency. This approach also lacks the ability to separate newcomers from misbehavers.. Uncertainty originates from information asymmetry and opportunism. It reflects whether a trustor has collected enough information from past interactions with a trustee and its confidence in that information. So in this paper the concept of uncertainty and its role in trust evaluation. It Propose a certainty-oriented reputation system. This present various proactive and reactive mobility assisted uncertainty reduction schemes.